TO VAD OR NOT TO VAD: That is the question. Improving the experience of receiving a Ventricular Assist Device (VAD). Issue 1 (June 2014) - Friedman, Emily; McMahon, Molly
As part of its Healthy Aging & Independent Living (HAIL) initiative, Mayo Clinic Center for Innovation (CFI) examined the patient experience regarding the decision to receive a ventricular assistive device (VAD) implant, and patients' quality of life after the surgery. As health care technology continues to develop, more people will be living longer, fuller lives with the assistance of wearable/implantable medical devices such as the VAD. This case study examined and made recommendations on ways for the Mayo Clinic VAD Committee to improve the program.